STRESS MANAGEMENT IN AYURVEDA WITH CONTEXT TO VEDAS - Dr. Deepak Sharma, Dr Jyoti Yadav (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2019)
The man of 21st century is living the life under various stresses, strains and anxiety. Stress is often explained in terms of characteristics of the environment that are disruptive to the individual. The father of stress research Hans Selye described, stress “the non-specific response of the body to any demand.” As we can say, the term ‘stress’ is difficult to define and it may differ people to people. According to Aacharya’s, Stress depends on Sattva. People with Pravara Sattva do not get stressed easily. Whereas People withAvara Sattva are more prone to stress.